Myeloid-derived suppressor cells in lymphoma: The good, the bad and the ugly. Issue 6 (November 2018) - Betsch, A.; Rutgeerts, O.; Fevery, S.; Sprangers, B.; Verhoef, G.; Dierickx, D.; Beckers, M.
Abstract: Lymphomas cause significant morbidity and mortality worldwide. A substantial number of patients ultimately relapse after standard treatment. However, the efficacy of these therapies can be counteracted by the patients' immune system, more specifically by myeloid-derived suppressor cells (MDSC). MDSC are a heterogeneous group of immature myeloid cells that suppress the innate and adaptive immune system via different mechanisms and accumulate under pathological conditions, such as cancer. MDSC play a role in the induction and progression of cancer and immune evasion. Increased numbers of MDSC have been reported in different lymphoma subtypes and are associated with a poor clinical outcome. This review aims to clarify the role of MDSC and their working mechanism in different lymphoma subtypes. Furthermore, the effect of MDSC on immunotherapies will be discussed.